Dampak Sistem Merger Bank Syariah Terhadap Eksistensi UMKM Di Indonesia - Jannah, Raodahtul (MADINAH, 2022)
Islamic banking as a financial distribution institution (financial intermediary) is currently growing rapidly and has become a pioneer in improving the economy in Indonesia. The development of Islamic banking in Indonesia has resulted in the realization of a merger or amalgamation of 3 state-owned Islamic banks, namely Bank Negara Indonesia Syariah (BNIS), Bank Rakyat Indonesia Syariah (BRIS), and Bank Syariah Mandiri (BSM) to become PT Bank Syariah Indonesia Tbk. The development of Micro small and Medium Enterprises in Indonesia really needs the contribution and role of Islamic banks in terms of increasing the availability of financing, namely providing easier requirements and conducting training and business assistance. Islamic banks are expected to continue to develop in improving the capabilities of small and medium enterprises, this is based on the fact that one of the roles of Micro small and Medium Enterprises can drive the national economy, namely being able to absorb large numbers of workers, increasing gross domestic product (GDP) and being able to overcome the economic crisis. The presence of Bank Syariah Indonesia will continue to provide support to Micro small and Medium Enterprises actors in Indonesia through products and various Islamic financial services that are in line with the needs of Micro small and Medium Enterprises.